Privacy in a Digital, Networked World : Technologies, Implications and Solutions - Zeadally, Sherali; Badra, Mohamad (Computer Communications and Networks,, 2015)
This comprehensive textbook/reference presents a focused review of the state of the art in privacy research, encompassing such diverse topics as cloud computing, crowdsourcing platforms, vehicular ad-hoc networks, big data, mobile devices, location-based systems, smart grid technology, databases, social networks, healthcare, behavioral economics, and peer-to-peer networks. The first book of its kind designed specifically to cater to courses on privacy, this authoritative volume provides technical, legal, and ethical perspectives on privacy issues from a global selection of renowned experts. Topics and features: Examines privacy issues relating to databases, P2P networks, big data technologies, social networks, and digital information networks Describes the challenges of addressing privacy concerns in various areas Reviews topics of privacy in electronic health systems, smart grid technology, vehicular ad-hoc networks, mobile devices, location-based systems, and crowdsourcing platforms Investigates approaches for protecting privacy in cloud applications Discusses the regulation of personal information disclosure and the privacy of individuals Presents the tools and the evidence to better understand consumers' privacy behaviors Offering invaluable support to undergraduate and graduate students, as well as instructors involved in courses on privacy, security and networking, this important work will also be of great interest to researchers and engineers working in the area of privacy. Dr. Sherali Zeadally is an Associate Professor in the College of Communication and Information at the University of Kentucky, Lexington, KY, USA. Dr. Mohamad Badra is an Assistant Professor in the College of Technological Innovation at Zayed University, Dubai, UAE.